Youth Perception on Online Teaching: Impact of COVID-19 Pandemic and Lockdown on Higher Education - Arora, Sudhanshu; Srivastava, Surya Pratap; Sahai, Ragini (Journal of Advanced Research in Humanities and Social Sciences, 2021)
The COVID-19 pandemic has affected all age groups of people around the world both physically and mentally but the impact of COVID-19 on youth, in particular, the university level students are long-lasting. In India the educational institutions and universities are closed indefinitely since March 2020 and they have introduced the process of teaching-learning through online and e-learning platforms. The compulsory learning through digitised mode and distance learning served as an alternative mechanism during pandemic. However, it missed the issues of physical interaction of students and instructors as well. It has also been a contributor towards increased level of stress and anxiety. The present study focuses on the perception of youth mainly the undergraduate and post graduate students on short-term and long-term impacts of the closure of campuses, online teaching, and covid-19 lockdown on university students in India. An online survey with 230 respondents in age group 18-30 years across various states was conducted to understand the research problem. Apart from physical and mental problems being faced by students, lack of gadgets and internet connectivity was also an important issue. The study concludes the need for the development of interventions and policies targeting youth and their mental health. How to cite this article:  Arora S, Srivastava SP, Sahai R. Youth Perception on Online Teaching: Impact of COVID-19 Pandemic and Lockdown on Higher Education. J Adv Res Humani Social Sci 2021; 8(2): 1-6. DOI:  https://doi.org/10.24321/2349.2872.202101